Influence of health system governance and leadership on service performance using an analytical cross sectional study design - A Syamsinar Asmi (Lembaga Edukasi Ilmiah Indonesia, 2026)
Introduction: Variability in health service performance persists despite structural investments, suggesting that governance and leadership are critical determinants. This study aimed to analyze the influence of health system governance and leadership on service performance within healthcare facilities. Methods: An analytical cross-sectional study was conducted among 210 health personnel selected using stratified random sampling. Data were collected using validated structured questionnaires measuring governance (accountability, transparency, participation, regulatory compliance) and leadership (transformational and transactional behaviors). Reliability was confirmed (Cronbach’s α ≥ 0.70). Descriptive statistics, bivariate tests (Chi-square), and multivariate logistic regression were applied to estimate adjusted associations. Statistical significance was set at α = 0.05. Results: Strong governance was significantly associated with good service performance (OR = 2.87; 95% CI: 1.58–5.21; p = 0.001). Effective leadership showed a stronger effect (OR = 3.45; 95% CI: 1.89–6.31; p < 0.001). Work experience ≥5 years was not statistically significant after adjustment (OR = 1.76; 95% CI: 0.98–3.15; p = 0.058). Facilities characterized by both strong governance and effective leadership demonstrated the highest likelihood of achieving optimal performance outcomes. Conclusion: Governance and leadership jointly determine service performance, with leadership exerting the greatest influence. Strengthening leadership capacity alongside reinforcing governance mechanisms is essential for improving healthcare delivery. Policy interventions should prioritize integrated strategies that align institutional frameworks with managerial effectiveness to achieve sustainable performance gains.